Effects of preservatives on the activities of salivary enzymes - Kim, Moon-Jung; Chang, Ji-Youn; Kim, Yoon-Young; Lee, Jae Wook; Kho, Hong-Seop (Pergamon Press Ltd., 2025)
Objectives To investigate the effects of common preservatives used in oral health care products on the enzymatic activities of lysozyme, peroxidase, and α-amylase in-solution and on-hydroxyapatite surface phases. Design The preservatives used in this study were sodium benzoate, methylparaben, propylparaben, and benzalkonium chloride. Hen egg-white lysozyme, bovine lactoperoxidase, and α-amylase from Bacillus sp. served as sources of purified enzymes. Human unstimulated whole saliva was used as a source of salivary enzymes. Hydroxyapatite beads were used as the surface phase. The preservatives were incubated with purified enzymes or saliva samples in-solution or on-hydroxyapatite surface phases, respectively. Enzymatic activities of lysozyme, peroxidase, and α-amylase were measured by hydrolysis of fluorescein-labelled Micrococcus lysodeikticus, oxidation of fluorogenic 2′,7′-dichlorofluorescin, and hydrolysis of fluorogenic starch, respectively. Results The effects of the preservatives on the enzymatic activities of lysozyme and peroxidase were more distinct in the saliva samples than purified substances, and in the in-solution phase than on-hydroxyapatite surface phase, and the opposite was true for α-amylase. The most significant result was apparent decrease in peroxidase activities caused by the parabens in the in-solution phase (P<0.05). Sodium benzoate and parabens inhibited lysozyme activity in the in-solution phase, but differently for the purified and salivary lysozymes. Parabens and benzalkonium chloride inhibited the enzymatic activity of α-amylase from Bacillus sp., not saliva samples, only on-hydroxyapatite surface (P<0.05). Conclusions Each preservative affected the enzymatic activities of lysozyme, peroxidase, and α-amylase differently. Based on the effects on salivary enzymes, sodium benzoate or benzalkonium chloride was recommended as preservatives rather than parabens.